Some observations to unconstitutional process - Hakansson Nieto, Carlos (2017)
The unconstitutional process at the Peruvian Constitution (1993) has a progressive development in the jurisprudence of his top judicial institution to make constitutional interpretations; but the Congress needs to take a politic decision to promote some amendments at the future.